Through the Looking Glass: Reflections of the Prodigal Daughter - Suthren, Carla (Early Theatre, 2024)
This contribution examines the submerged prodigal daughter plot within the dominant ‘prodigal son’ drama of Gascoigne’s Glass of Government (1575). Jerry Aline Flieger has suggested that we might reimagine the prodigal daughter not as merely ‘going beyond the fold of restrictive paternal law, only to return’, but as ‘lush, exceptional, extravagant, and affirmative … to be prodigal in this sense is to alter the law, to enlarge its parameters and recast its meaning’. Instead of marginalizing and banishing the prodigal daughter, this article suggests that it may be worth passing through Gascoigne’s looking glass to imagine an alternative space for her to occupy.